Optimization of continuous flow pulsed light system process parameters for microbial inactivation in tender coconut water, pineapple and orange juice. (27th December 2022) - Preetha, P.; Varadharaju, N.; Jeevarathinam, G.; Deepa, J.; Kumar, A. P. Mohan; Balakrishnan, M.; Rajkumar, P.; Pandiselvam, R.
Abstract: Continuous flow pulsed light (PL) system was designed and fabricated with a residence time of 3.5 s at a flow rate of 100 ml/min to study the effect on microbial quality of the fruit juice. The circuit was designed to deliver pulse energy between 12.6 and 756 J/cm 2 with a flash lasted 360 μs at a frequency of three pulses per second. Tender coconut water, pineapple and orange juice was treated with different input voltage (500–1000 V) to the lamp, distance of the lamp exposed to the sample (5–15 cm) and treatment time (15–45 s) to reduce the population of aerobic plate count (APC), yeast and mold. Box–Behnken design (BBD) was used to optimize the PL process parameters. The process condition was optimized based on the microbial reduction rate. The optimized condition was input voltage of 1492, 1499, and 1486 V, distance of 7.6, 10.2, and 5.3 cm, and treatment time of 43 s (12 passes), 44 s (13 passes), and 45 s (13 passes) for tender coconut water, pineapple and orange juice, respectively at the target of five log reduction for APC and four log reduction for Y&M. These results recommend that a continuous flow PL system could improve the microbial safety of the fruit juice. PL is a nonthermal method for inactivating food microbes, extending food's shelf life. For industrial purposes, the batch system is virtually impossible. As a result, continuous flow systems for liquid foods can provide a better way to handle large volumes. The optimized setup was found to achieve a microbial death rate of at least 5 log CFU/ml, consistent with FDA guidelines for fruit juice. The BBD of response surface methodology helps in optimizing the process parameters such as input voltage of the lamp, distance of the PL lamp to treatment tube and treatment time. The resulting mathematical model provides the PL process conditions for designing the equipment for different fruit beverages to obtain microbiologically safe products. Abstract :